A novel resource selection framework to improve QoS in computational grid. (1st January 2014) - Kavitha, G.; Sankaranarayanan, V.
The computational grid is organised as a collection of heterogeneous resources to solve complex computational problems in scientific domains. The fundamental issue to be addressed here is the selection of appropriate compute and network resources for every submitted job. We present a novel resource selection framework, which selects trusted resources across multiple resource sites based on the computation and network capacity of the resource. We developed a new scheme for efficient data transfer in high latency wide area networks. To efficiently utilise the bandwidth of the connected resources, an improvement over the existing TCP is proposed. TCP striping aims at minimising the communication time and maximising the network utilisation. We have solved the problem of finding the optimal number of stripes considering the available bandwidth and data file size. Simulation results have shown that the proposed work completes the submitted jobs with a minimum communication time and execution time. Also, there is a significant improvement of bandwidth utilisation in high bandwidth high latency networks.